Mark's Calculations For Machine Design - H.Brown Thomas (MC Graw Hill, 2005)
Everyday Engineers must solve some of the most difficult design problems and often with little time and money to spare. It was with this in mind that this book was designed. Based on the best selling Mark’s Standard Handbook for Mechanical Engineers, Mark’s Standard Engineering Calculations For Machine Design offers a detailed treatment of topics in statics, friction, kinematics, dynamics, energy relations, impulse and momentum, systems of particles, variable mass systems, and three-dimensional rigid body analysis. Among the advanced topics are spherical coordinates, shear modulus tangential unit vector tension, deformable media, and torsion (twisting).